The role of human capital in improving economic growth in the conditions of transitive economy. (Journal of Economic Research & Business Administration, 2015)
The article considers the problem questions of the use of human resources as the main factor of increasing economic growth in the socio - economic reforms in the Kyrgyz Republic.